Предмет: Алгебра,
автор: Аноним
Спростіть вираз : (3m-4n)(3m+5n)-(4,5m-n)(2m+4n)
Ответы
Автор ответа:
0
( 3m - 4n )( 3m + 5n ) - ( 4,5m - n )( 2m + 4n ) = 9m² + 15mn - 12mn - 20n² - ( 9m² + 18mn - 2mn - 4n² ) = 9m² - 20n² + 3mn - ( 9m² - 4n² + 16mn ) = 9m² - 20n² + 3mn - 9m² + 4n² - 16mn = 24n² - 13mn
Похожие вопросы
Предмет: Математика,
автор: jurij1234567890
Предмет: История,
автор: sbojkofdhjbvghk
Предмет: Алгебра,
автор: olgaxaraxoriba
Предмет: Физика,
автор: alina200164
Предмет: Математика,
автор: polinaBulaVka